Leachability Characteristic of Heavy Metals and Associated Health Risk Study in Typical tin Mine Tailings - Chen, Shouyue; Wang, Zhongzhen; Zhang, Di; He, Zhaohui; Luo, Yong; Li, Ruida; Cheng, Haifan; Liu, Yang; Zhang, Ying (Bulletin of environmental contamination and toxicology, 2025)
In this study, the leachability characteristics of heavy metals (Pb, Cu, Ni, As, and Cd) in tailing-contaminated soils were analyzed to assess contamination levels and health risks. The distribution and sources of heavy metals were also examined. Our findings revealed that, although currently the exposed tailings themselves posed minimal risk of leaching, the soils in the mine vicinity were significantly contaminated with Pb, Cu, As, and Cd as the result of nearly 100 years of mining history. With increasing soil depth (0–4, 4–6, 6–10 m), the concentrations of these heavy metals (excluding Ni) exhibited an initial rise followed by a sharp decline. Furthermore, APCS-MLR (absolute principal component score-multiple linear regression) model indicated that Cd, Pb, Cu, and As were primarily influenced by mining activities, whereas Ni was predominantly determined by the soil parent material. Health risk assessments highlighted that As was a major contributor to carcinogenic and non-carcinogenic risks, and children were at higher risk than adults.